PEMBERDAYAAN PETANI MELALUI GAPOKTAN DI DESA SUMBERMULYO, BANTUL - , ARNOLD SIA HANANJA SIAGIAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The establishment of Gapoktan Sumber Harapan is the first step to upgrade the ability each of its members in carrying out their functions, develop agribusiness and strengthen farmer groups become strong and independent organization. Capacity enhancement and skill of farmer is essentially an empowerment. As for strategy conducted in the process of farmer empowerment is give authority and developing of farmer capacity. The process of strengthening and independence on farmer or farmer group turned out to be not as easy as expected. This is caused by mindset of farmers are still the same as before, that is expect help. Until now, the doctrine of âreliefâ for farmer already attached with very strong, so farmer into dependency and not participatory in carrying out agricultural development. This research aims to analyze the strategy undertaken by the Gapoktan Sumber Harapan in empowering its members and describe the capacity owned by Gapoktan Sumber Harapan as a media to empowering its members. This research using qualitative research methods. By using qualitative research methods, researcher enabled to understand and explain reality as a whole. The result of this research concluded that Gapoktan Sumber Harapan did a series of strategies to expediting the process of empowerment, of which is to increase the farmer/members participation, capture the farmer/members aspiration and invite the farmer/members to sit in a seminars and exhibitions of agricultural. The strategy conducted by Gapoktan Sumber Harapan to empowering its members are supported by Gapoktan capacity functioning as : 1) Production units, 2) Agricultural production facilities units, 3) Processing units, 4) Marketing units and 5) Microfinance units. Meanwhile, Gapoktan Sumber Harapan effectiveness can be seen from some of the following criteria, as : increased production, adaptability, job satisfaction, ability to profit and search resources. Keywords : Gapoktan Sumber Harapan, Empowerment Strategy, Capacity, Effectiveness